2020
DOI: 10.1101/2020.02.13.947598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MSH1 is required for maintenance of the low mutation rates in plant mitochondrial and plastid genomes

Abstract: 2Mitochondrial and plastid genomes in land plants exhibit some of the slowest rates of sequence 3 evolution observed in any eukaryotic genome, suggesting an exceptional ability to prevent or correct 4 mutations. However, the mechanisms responsible for this extreme fidelity remain unclear. We tested 5 seven candidate genes involved in cytoplasmic DNA replication, recombination, and repair (POLIA, 6 POLIB, MSH1, RECA3, UNG, FPG, and OGG1) for effects on mutation rates in the model 7 angiosperm Arabidopsis thali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(110 citation statements)
references
References 74 publications
7
102
1
Order By: Relevance
“…The edited rps8 transcripts generate RPS8 protein with altered amino acid hydrophobicity, suggesting that RNA editing at rps8 -182 improves low-temperature tolerance in rice by moderating the stability of RPS8 protein under low-temperature conditions [ 76 ]. Chloroplast genomes have very slow rates of sequence evolution, averaging ~5-fold slower than nuclear genomes [ 108 , 109 ], suggesting that chloroplast RNA editing evolved to improve low-temperature tolerance by increasing protein stability.…”
Section: Chloroplast Gene Expression and Environmental Stressmentioning
confidence: 99%
“…The edited rps8 transcripts generate RPS8 protein with altered amino acid hydrophobicity, suggesting that RNA editing at rps8 -182 improves low-temperature tolerance in rice by moderating the stability of RPS8 protein under low-temperature conditions [ 76 ]. Chloroplast genomes have very slow rates of sequence evolution, averaging ~5-fold slower than nuclear genomes [ 108 , 109 ], suggesting that chloroplast RNA editing evolved to improve low-temperature tolerance by increasing protein stability.…”
Section: Chloroplast Gene Expression and Environmental Stressmentioning
confidence: 99%
“…Total cellular DNA was stored at -20°C until all 9 replicates were processed. Then, Duplex Sequencing libraries were created for all 9 samples, following our previously described protocols (Wu et al 2020) with some modifications. Briefly, DNA was fragmented with a Covaris M220 Focused-Ultrasonicator, end repaired (NEBNext End Repair Module), and A-tailed (Klenow Fragment Enzyme, 1mM dATP).…”
Section: Duplex Library Preparation and Mtdna Enrichmentmentioning
confidence: 99%
“…An alternative to MA experiments has emerged in the form of high-fidelity sequencing techniques that can detect mtDNA variants segregating in tissues at extremely low frequencies (Salk et al 2018;Sloan et al 2018). One technique called Duplex Sequencing (Schmitt et al 2012;Kennedy et al 2014) is particularly useful for this application as it is highly accurate with error rates as low as ~210 -8 per bp (Wu et al 2020), facilitating detection of de novo mtDNA mutations essentially as they occur. Duplex Sequencing works by tagging both ends of library molecules with random barcodes before they are amplified and sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that giant viruses acted as vectors of mtMutS into octocoral mitochondria does have some additional support. First, HGT from giant viruses has likely happened one more time in the MutS family of proteins, with the transfer of pMSH1 in land plants [41]. Second, giant viruses are among the main groups of viruses found on the octocoral Gorgonia ventalina [42,43,44] and MutS orthologues from giant viruses are abundant in marine environments [24].…”
Section: The Hgt Origin Of Octocoral Mtmutsmentioning
confidence: 99%
“…By contrast, most closely related homologues of pMSH1 are found in giant viruses [15]. A recent study showed that pMSH1 is dual-localized to mitochondria and chloroplast and involved in mismatch repair [15], while the role of yeast MSH1 in MMR remains controversial [16,17,18]. Within animals, the lack of a mitochondria-targeted MutS homologues suggests that organellar MMR may be absent.…”
Section: Introductionmentioning
confidence: 99%